2019
DOI: 10.1021/acs.jmedchem.8b01597
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Janus Kinase (JAK) and Histone Deacetylase (HDAC) Dual Inhibitors for the Treatment of Hematological Malignancies

Abstract: Concurrent inhibition of Janus kinase (JAK) and histone deacetylase (HDAC) could potentially improve the efficacy of the HDAC inhibitors in the treatment of cancers and resolve the problem of HDAC inhibitor resistance in some tumors. Here, a novel series of pyrimidin-2-aminopyrazol hydroxamate derivatives as JAK and HDAC dual inhibitors was designed, synthesized, and evaluated, among which 8m possessed potent and balanced activities against both JAK2 and HDAC6 with half-maximal inhibitory concentration at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 43 publications
1
47
0
Order By: Relevance
“…The data set of 29 pyrimidin‐2‐aminopyrazol‐hydroxamate JAK2 inhibitors was used for the modeling study . The compounds were sketched and energy minimized using Sybyl‐X 2.1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data set of 29 pyrimidin‐2‐aminopyrazol‐hydroxamate JAK2 inhibitors was used for the modeling study . The compounds were sketched and energy minimized using Sybyl‐X 2.1.…”
Section: Methodsmentioning
confidence: 99%
“…3D‐QSAR study was performed based on the 29 pyrimidin‐2‐aminopyrazol‐hydroxamate JAK2 inhibitors reported by Liang et al . The compounds and their corresponding activity values (pIC 50 ) were shown in Table .…”
Section: D‐quantitative Structure Activity Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…In analogous studies by three independent groups, the hybrids 20 – 22 were also shown to display dual JAK/HDAC inhibition with a degree of selectivity towards HDAC6 [ 144 , 145 , 146 ]. Alike pacritinib in the synthesis of 19 , each work utilised a JAK (or JAK2-selective) inhibitor containing an aminopyrimidine unit flanked by two hydrophobic aromatic groups—crucial for binding to the hinge region of the JAK active site.…”
Section: Class-ii Hdac Dual Inhibitorsmentioning
confidence: 99%
“…A lot of literatures have described the synergistic and additive effects by the joint use of HDACs inhibitors and vari-ous antitumor agents. [13][14][15] Recently, Emmons et al revealed that HDACs inhibitor could enhance the durability of BRaf inhibitor therapy. 16) Hence, the development of BRaf V600E and HDACs dual inhibitors maybe a valuable strategy to circumvent resistance.…”
Section: Introductionmentioning
confidence: 99%